Literature Review: Factors Associated with Hepatitis a Prevention Among Students in the School Environment - Jatu Laksmita; Meni Anggrayani (CV. AFDIFAL MAJU BERKAH, 2026)
Hepatitis A represents a significant public health concern among student populations in Indonesia with considerably high prevalence rates. This study aimed to identify and analyze factors associated with hepatitis A prevention among students through systematic literature review. A systematic review was conducted on 20 research articles published between 2020-2024 using cross-sectional, case-control, and pre-experimental designs with total samples ranging from 36 to 835,256 respondents. Factors demonstrating the strongest associations included handwashing with soap behavior (OR=7.90), personal hygiene (OR=5.71), history of contact with patients (OR=9.92), unsafe food consumption (OR=10.545), unhygienic toilet use (OR=10.500), and communal eating habits (OR=21.48). Knowledge showed significant correlation with prevention practices (p<0.05), while attitude demonstrated inconsistent results. Immunization status emerged as the most effective protective factor with risk reduction up to 94.4% (OR=0.056). Socioeconomic factors and school environmental conditions served as structural determinants. Hepatitis A prevention among students requires a comprehensive multi-level approach integrating health education, school sanitation improvement, food safety monitoring, clean and healthy lifestyle promotion, and vaccination programs